Nineteen Eighty-Four Based on a Novel by George Orwell - Orwell, George (BFI, 2022)
"Nineteen Eighty-Four" is a British television adaptation of the 1949 novel of the same name by George Orwell, originally broadcast on BBC Television in December 1954. The production proved to be hugely controversial, with questions asked in Parliament and many viewer complaints over its supposed subversive nature and horrific content. In a 2000 poll of industry experts conducted by the British Film Institute to determine the 100 Greatest British Television Programmes of the 20th century, "Nineteen Eighty-Four" was ranked in seventy-third position. [en.wikipedia.org]